Impulsive and risky decision-making in adolescents with attention-deficit/hyperactivity disorder (ADHD): The need for a developmental perspective. (April 2022) - Dekkers, Tycho J.; de Water, Erik; Scheres, Anouk
Abstract: Impulsive and risky decision-making peaks in adolescence, and is consistently associated with the neurodevelopmental disorder Attention-Deficit/Hyperactivity Disorder (ADHD), regardless of age. In this brief review, we demonstrate the similarity of theoretical models explaining impulsive and risky decision-making that originate in two relatively distinct literatures (i.e., on adolescence and on ADHD). We summarize research thus far and conclude that the presence of ADHD during adolescence further exacerbates the tendency that is already present in adolescents to make impulsive and risky decisions. We also conclude that much is still unknown about the developmental trajectories of individuals with ADHD with regard to impulsive and risky decision making, and we therefore provide several hypotheses that warrant further longitudinal research. Highlights: ADHD exacerbates risky and impulsive decision making in adolescents. Developmental trajectories of impulsive and risky decision making in ADHD are unknown. Different developmental trajectories are hypothesized.